Contrasting Meteorological Drivers of the Glacier Mass Balance Between the Karakoram and Central Himalaya - Bonekamp, Pleun N. J.; de Kok, Remco J.; Collier, Emily; Immerzeel, Walter W. (Frontiers in Earth Science, 2019)
There is strong variation in glacier mass balances in High Mountain Asia. Particularly interesting is the fact that glaciers are neutral or even gaining mass in the Karakoram and Kunlun Shan ranges, which is in sharp contrast with the negative mass balances in the rest of High Mountain Asia. To understand this difference, an in-depth understanding of the meteorological drivers of the glacier mass balance is required. In this study, two catchments in contrasting climatic regions, one in the central Himalaya (Langtang) and one in the Karakoram (Shimshal), are modelled at 1 kilometer grid spacing with the numerical atmospheric model WRF for the period of 2011 to 2013. Our results show that the accumulation and melt dynamics of both regions differ due to contrasting meteorological conditions. In Shimshal, 92% of the annual precipitation falls in the form of snow, in contrast with 42% in Langtang. In addition, 80% of the total snow falls above an altitude of 5000 m a.s.l., compared with 35% in Langtang. Another prominent contrast is that most of the annual snowfall falls between December and May (71%), compared with 52% in Langtang. The melt regimes are also different, with 41% less energy available for melt in Shimshal. The melt in the Karakoram is controlled by net shortwave radiation (r=0.79 ± 0.01) through the relatively low glacier albedo in summer, while net longwave radiation (clouds) dominates the energy balance in the Langtang region (r=0.76 ± 0.02). High amounts of snowfall and low melt rates result in a simulated positive glacier surface mass balance in Shimshal (+0.31±0.06 m w.e. yr-1) for the study period, while little snowfall and high melt rates lead to a negative mass balance in Langtang (-0.40±0.09 m w.e. yr-1). The melt in Shimshal is highly variable between years, and is especially sensitive to summer snow events that reset the surface albedo. We conclude that understanding glacier mass balance anomalies requires quantification and insight into subtle shifts in the energy balance and accumulation regimes at high altitude and that the sensitivity of glaciers to climate change is regionally variable.